Relação da salinidade e turbidez nos limites de um estuário amazônico - VALENTIM, Micaela Machado (2019)
This study relates salinity and turbidity fluctuations along the Mojuim estuary, dominated by macrotidal and located in the humid tropical climate region between the mouth of the Pará river and the Atlantic Ocean, (0° 39’43.53’’S and 48° 0’4.86’’O), Northeast of Pará, Brazil. The salinity and turbidity data were measured in the surface and bottom water column in situ with a multiparameter probe (Horiba U-50), in six months, corresponding to the intermediate period (July and August, 2016), dry period (November and December, 2016) and rainy (January and February, 2017), during the spring tide. The sampling stations covered 50 km along the estuary and were divided into five sectors with 10 km each. We classify the sectors according to the Venice System. We did not observe significant variations (p>0.5) of salinity in the water column, the opposite occurs for turbidity. Qualitative-quantitative questionnaires were applied to communities located in different extensions of the Mojuim estuary, in order to detect the environmental perception of the residents about the saline intrusion. In the rainy season, we observed the lowest average salinity (8.5 ± 0.8 PSU) and the highest turbidity (344.32 ± 48.22 NTU), in the intermediate period the salinity was 15.99 ± 0.37 PSU and the turbidity was 173, 91 ± 19.26 NTU, the highest salinity and turbidity, which were 22.38 ± 0.61 PSU and 215.16 ± 42.09 NTU respectively, occurred in the dry period. The saline intrusion reached sector 5 (50 km of upstream mouth) in the dry period and was restricted to sector 3 (30 km) in the rainy season. The last one, in all periods, presented the greatest variation in the haline zones, which varied from oligohaline in the rainy period, mesohaline in the intermediate and polyhaline in the dry. The environmental perception of the interviewees indicated changes in the river, highlighting aspects such as: decrease of black water, presence of brackish water in the fluvial upstream portion. We noticed that during the rainy and intermediate periods, the fluvial domain limits the advance of the tide, therefore, the sector 5 does not present halinas variations, remaining as fresh water zone. The opposite occurs in the dry period, when this sector presents oligohaline zone, due to the greater reach of the tide and the greater dispersion of the salts in the estuary. These haline limits may vary inter annually, indicating the influence of climatological anomalies on the estuary dynamics in recent years.